2017
DOI: 10.1017/jmo.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

How ambidextrous organizational culture affects job performance: A multilevel study of the mediating effect of psychological capital

Abstract: Ambidexterity organization, which is defined as the ability of an organization to simultaneously pursues exploration and exploitation, has received attention by researchers who have examined its beneficial effect on organizational performance and success. This study attempted to examine the positive effect of ambidextrous organization culture (AOC), which is regarded as the core characteristic of ambidextrous organizations by using a multilevel model. Specifically, this study examined the effects of AOC on mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…In that sense, our findings offer validation to literature suggesting that successful employees nowadays need to be ambidextrous, in other words, not only able to grow and develop, but also to do so in a way that shows awareness of dangers and a concern for efficiency (Kao & Chen, 2016). Such employees can reach maximum performance (Lee et al, 2019) and become assets for their organizations (Ybema et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, our findings offer validation to literature suggesting that successful employees nowadays need to be ambidextrous, in other words, not only able to grow and develop, but also to do so in a way that shows awareness of dangers and a concern for efficiency (Kao & Chen, 2016). Such employees can reach maximum performance (Lee et al, 2019) and become assets for their organizations (Ybema et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In line with Han et al [41], the group with ambidextrous organizational culture (i.e., adaptive and consistent culture) emphasized the individual subjectivity to make choices and to develop themselves, and allowed the task-related differences to be congruent with the organizational norms. According to Junni et al [42] and Lee et al [43], the ambidextrous organizational culture have shown positive effects on the organizational performance. Furthermore, such ambidextrous culture constructed by the adaptive culture and consistent culture or shared vision and organizational diversity, was regarded as a causal organizational resource for organizational outcomes [10,19,41].…”
Section: Organizational Ambidexterity Ambidextrous Leadership and Cumentioning
confidence: 99%
“…P sychological Capital (PsyCap) reflects an 'individual's positive psychological state of development,' characterized by the psychological resources of hope, self-efficacy, resilience and optimism (Luthans, Youssef, & Avolio, 2007: 3). Previous research suggests it is an important predictor of desirable outcomes including job performance, job satisfaction, work-family enrichment, organizational commitment and psychological well-being (e.g., Avey, Reichard, Luthans, & Mharte, 2011;Lee, Seo, Jeung, & Kim, 2017;Mishra, Bhatnagar, Gupta, & Wadsworth, 2017). Although PsyCap has mainly been examined at the individual level, a small number of studies have demonstrated positive associations between team-level PsyCap and team performance (Clapp-Smith, Vogelgesang, & Avey, 2009;Peterson & Zhang, 2011;Mathe, Scott-Halsell, Kim, & Krawczyk, 2017).…”
Section: Introductionmentioning
confidence: 99%